Impact of Chronic Periodontitis on Insulin Resistance in Patients with Type 2 Diabetes Mellitus - Abbasova, Esmira Mirahmad; Guliyev, Musa Elshad; Yagubova, Susan Nazim (Actual Dentistry, 2026)
Chronic periodontitis is among the most prevalent inflammatory diseases of periodontal tissues, characterized by progressive destruction of tooth-supporting structures that may ultimately lead to tooth loss. Growing evidence suggests that periodontal inflammation is closely linked to systemic metabolic disorders, including type 2 diabetes mellitus (T2DM). Objective. To assess the impact of chronic periodontitis on the development of insulin resistance in patients with T2DM, with particular attention to alterations in the periodontal microbiota. Materials and Methods. Ninety individuals were examined and divided into three groups: patients with T2DM and chronic periodontitis, patients with chronic periodontitis but without diabetes, and a control group of systemically and periodontally healthy individuals. Clinical periodontal assessment and polymerase chain reaction (PCR) analysis of periodontal pathogens were performed. Results. Patients with both T2DM and chronic periodontitis exhibited a predominance of first- and second-order periodontal pathogens, accompanied by heightened inflammatory activity and reduced insulin sensitivity. Conclusions. Chronic periodontitis in patients with type 2 diabetes mellitus contributes to systemic metabolic disturbances and necessitates a comprehensive interdisciplinary approach to diagnosis and treatment.